Tinjauan Realitas Virtual dan Game Serius dalam Terapi Perilaku Kognitif untuk Gangguan Kecemasan Sosial - Pattiasina, Timothy John; Ar Rosyid, Harits; Handayani, Anik Nur; Junaedi, Hartarto; Trianto, Edwin Meinardi (Jurnal Pekommas, 2024)
This literature review discusses efforts to enhance cognitive behavioral therapy in addressing social phobia, such as social anxiety disorder, by utilizing serious games and virtual reality exposure therapy. In the worldwide context of the COVID-19 outbreak, conventional cognitive behavioral therapy faces significant challenges, prompting practitioners and researchers to seek innovative e solutions. During the conducted literature review, several research articles were identified that explore the utilization of virtual reality exposure therapy and serious games within the stages of cognitive behavioral therapy. Using the PICOC method and software such as Publish or Perish, Zotero, and VOSViewer, 30 journal articles have been obtained, indicating that virtual reality exposure therapy and serious games can enhance the effectiveness of cognitive behavioral therapy. However, there are clear signs suggesting that integrating virtual reality (VR) technology and serious games on smartphones into the cognitive behavioral therapy process could offer a promising avenue for new research. This approach may help address the challenges brought about by the effects of the COVID-19 pandemic on people with social anxiety disorder, particularly in Indonesia. Although further research and therapy adaptation according to the cultural context in Indonesia are needed, this development offers new research opportunities as an alternative therapeutic approach with significant advancements in addressing social anxiety disorder.